Sexual Dimorphism in Scavenging Muscovy Ducks (Cairina moschata): Differences in their Growth Traits, Physiological and Haemato-Biochemical Parameters - Oyeleye, Olubisi O.; Adeoye, Adelani A.; Osunkeye, Olumuyiwa J.; Akinola, Mercy M. (Syiah Kuala University, 2025)
The Muscovy duck (Cairina moschata) is a widely distributed domestic waterfowl species known for its adaptability and scavenging behaviour. This study investigates the impacts of sex on growth traits, physiological, and haemato-biochemical parameters in scavenging adult Muscovy ducks. 100 adult Muscovy ducks (27 males and 73 females) were sampled from free-ranging scavenging populations. Data were collected on growth traits, physiological and haemato-biochemical parameters. The data collected were subjected to t-test and correlation analyses. The results showed significant sexual dimorphism in growth traits, with male Muscovy ducks consistently outperforming females. Body temperature and rectal temperature did not show a significant (p0.05) difference. Significant (p0.05) differences in heartbeats and respiratory rates were observed. Males exhibited higher mean values for PCV, RBC, Hb, WBC, and MCHC. Females demonstrated higher mean values for platelets, MCV, MCH and Neutrophils. Serum biochemical parameters showed no significant effect (p0.05) in all the variables except in urea, in which males had a higher value. Sex-related variations are essential for optimizing management practices, assessing health status, and increasing the productivity of Muscovy ducks.